(untitled) - Wegmann, Brenda (New York, 1990)
Mosaic One: A Reading Skills Book, 3/e, presents three to four authentic reading selections per chapter in an effort to help students develop skills for reading in a meaningful rather than a mechanical way. This approach enables students to successfully tackle other academic texts. Ideal for intermediate to high-intermediate students.
Keywords: English language,English language; Textbooks for foreign speakers.,Reading